2006
DOI: 10.1139/b06-036
|View full text |Cite
|
Sign up to set email alerts
|

Response of red-osier dogwood (Cornus sericea) seedlings to NaCl during the onset of bud break

Abstract: A greenhouse study was designed to test the response of red-osier dogwood (Cornus sericea L.) to NaCl during the onset of bud break. Seedlings treated with 50 mmol·L–1 NaCl for 32 d had lower shoot dry mass and shoot height than untreated seedlings. Transpiration and photosynthetic rates, chlorophyll b and carotenoid concentrations of red-osier dogwood seedlings were significantly reduced by NaCl treatment. The shoots of seedlings treated with 50 mmol·L–1 NaCl had a higher bulk modulus of cell wall elasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…The reduction of the total carotenoid content was observed in all the centaury shoots cultured in mediums supplemented with >50-mM NaCl. The obtained results agreed with those reported in Hordeum vulgare [68], Salvinia molesta [69], Cornus sericea [70], and melons [19]. Salt stress induced the degradation of β-carotene, which further resulted in a decreased carotenoid content [71].…”
Section: Discussionsupporting
confidence: 89%
“…The reduction of the total carotenoid content was observed in all the centaury shoots cultured in mediums supplemented with >50-mM NaCl. The obtained results agreed with those reported in Hordeum vulgare [68], Salvinia molesta [69], Cornus sericea [70], and melons [19]. Salt stress induced the degradation of β-carotene, which further resulted in a decreased carotenoid content [71].…”
Section: Discussionsupporting
confidence: 89%
“…Tatarian dogwood might be considered a salt-sensitive species. Red-osier dogwood (Cornus stolonifera) were also sensitive to salt stress, and the seedlings treated with 50 mmol • L -1 NaCl for 30 d became 16% shorter and accumulated 39% less shoot dry mass than the control (Mustard and Renault, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Red-osier dogwood (Cornus stolonifera) has been reported to be moderately resistant to salt stress in a number of investigations (Davis et al, 2014;Mustard and Renault, 2004;Renault and Affifi, 2009). In a greenhouse study, the changes in the cell wall composition and elasticity of red-osier dogwood (Cornus sericea) under drought stress were attributed to the delay in breaking bud (Mustard and Renault, 2006). Dale et al (2003) found that water deficit enhanced the freeze-tolerance of red-osier dogwood.…”
mentioning
confidence: 99%
“…Both salt concentrations (50 and 100 mM NaCl) significantly decreased plant height 39.9 cm and 41.7 cm, respectively compared to HO. Many studies had reported and agreed that salt stress caused similar plant height reduction in watermelon (Yetisir and Uygur, 2009); in pepper (Aktas et al, 2006); in maize (Irshad et al, 2002); in muskmelon (Carvajal et al, 1998); in tomato (Casierra-Posada et al, 2009); in common bean (Beltagi et al, 2006); in red-osier dogwood (Cornus sericea) (Mustard and Renault, 2006); in common bean (Gama et al, 2007). In the study, HA caused an increase in plant heights in both salt treated plants, which were 17% and 9.8% taller in S1HA1 and S2HA2, respectively compared to S1 and S2, but these differences were not significant at the level of α=0.05 (Table 3).…”
Section: Effect Of Nacl and Ha On Growth Parameters And Of Mung Bean mentioning
confidence: 95%